On the reliability of sense perceptions in Epicurean epistemology - Schneider, Zeev (University of Ottawa (Canada), 2009)
In this thesis I advance an interpretation of the statement, famously attributed to Epicurus by several ancient sources, 'all perceptions ( aistheseis or phantosia) are true (alethes).' The statement earned Epicurus and his followers the scorn and ridicule of prominent non-Epicurean figures, including Cicero and Plutarch, and has remained the subject of scholarly controversy. The interpretation I advance in this thesis is oriented around the foundational role of perceptions in Epicurean epistemology. Though they are themselves irrational (alogos), perceptions are both the basis of all reasoning and criteria of truth in Epicurus' system. To show how all perceptions are true in this role, I analyse the causal mechanism of perception and show that the content of each perception is basic and irreducible: no perception can contradict another and all are equally reliable as evidence. Thus, on my reading, the truth of all perceptions refers to their reliability in Epicurus' method.
Keywords: Philosophy.